Exploring Culinary Identity: The Intersection of Tradition and Modern Influences in China and Bangladesh - A K M Rezown Mahmud; Waheduzzaman (Journal of Social Growth and Development Studies, 2025)
This research focuses on food practices, cultural significance and gastronomic identity within China and Bangladeshis cuisines. Two very different countries have their own food culture and live on a diet shaped by history, climate and income level. Meanwhile, food culture is examined in both societies through changes in traditional recipes and modes of preparation. Food rituals and meal symbols are some of the areas researchers looked at as well (to understand) The social importance of meals and how these food practices influence household and family consciousness. The study also looks at the impact of globalization on Chinese and Bangladeshi cuisine, finding that both countries updated its old dishes in response to modern trends to seek new markets abroad. What does this research find? How food cultures in these countries have developed and continue to define social identity. This comparative study represents one aspect of the relationship between food and identity; culture It underscores the importance of food in cultural exchange on a global level.